Extracorporeal Shock Waves Therapy for the Treatment of Acute and Chronic Wounds—A Prospective, Monocentric Clinical Trial to Examine the Effect of Shock Waves on Wound Healing - Kristina Landscheidt; Ahmed Alabdulmohsen; Markus Hübscher; Benjamin Geber; Jochen‐Frederick Hernekamp; Ole Goertz (Health Science Reports)
ABSTRACT Introduction The aim of our prospective blinded clinical study was to examine a possible improvement and acceleration of epithelialization by treatment with low‐energy extracorporeal shock waves on skin graft donor and recipient sites in patients with chronic wounds. In addition, several secondary parameters were investigated to evaluate the compatibility of the therapeutic method, its influence on infection occurrence and bacterial colonization. Materials and Methods A total of 35 patients were included in the study. Of these, 25 participants were assigned to the verum‐placebo group and 10 to the sham treatment group. The study of the sham control group was done to exclude a possible “remote effect” of the placebo area. Depending on the group, the wound areas were treated with low‐frequency shock waves, placebo, or sham. The examinations were performed immediately on Day 0 after surgical treatment and on Days 5, 7, 9, and 12 after surgery. To record long‐term results, an additional evaluation of the wound situation was performed on Day 90. Results Epithelialization was statistically significantly accelerated by shock wave application at both skin graft recipient sites and donor sites (0.86 vs. 0.92, p < 0.05). Furthermore, the risk of wound infection was significantly reduced by using extracorporeal shock waves. Serious side effects were not reported. Conclusion A repeated application of ESWT followed by standardized wound care was shown to significantly accelerate the time to re‐epithelialization at the skin graft donor and recipient site compared with re‐epithelialization time in patients of the sham/placebo group.